The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3989/cyv.2005.v44.i2.387
|View full text |Cite
|
Sign up to set email alerts
|

Varistores cerámicos basados en óxido de cinc

Abstract: Los varistores basados en ZnO son dispositivos electrocerámicos caracterizados por una elevada respuesta eléctrica no lineal, que se origina en una microestructura funcional con unas características bien definidas. En el presente artículo de revisión se examina como ha tenido lugar el desarrollo de estos materiales desde su descubrimiento a principios de los años 70. No obstante, a pesar del importante avance tecnológico registrado desde entonces, numerosos aspectos básicos relacionados con su microestructura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…According to the mapping of elements, it is observed that both the spinel phase (Zn 7 Sb 2 O 12 ) and the Bi-rich phase are segregated in the grain boundaries, and that Cr, Mn and Ni are mainly associated with the spinel phase, while Co is observed associated with both grains and grain boundaries. It has been indicated that the determining oxides in the high temperature reactions are ZnO, Bi 2 O 3 and Sb 2 O 3 , and that the rest of the dopants only act as secondary elements that dissolve and are incorporated into different phases formed [32]. Figure 6 shows the cross-sectional appearance and element mapping of the base ceramic varistor.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…According to the mapping of elements, it is observed that both the spinel phase (Zn 7 Sb 2 O 12 ) and the Bi-rich phase are segregated in the grain boundaries, and that Cr, Mn and Ni are mainly associated with the spinel phase, while Co is observed associated with both grains and grain boundaries. It has been indicated that the determining oxides in the high temperature reactions are ZnO, Bi 2 O 3 and Sb 2 O 3 , and that the rest of the dopants only act as secondary elements that dissolve and are incorporated into different phases formed [32]. Figure 6 shows the cross-sectional appearance and element mapping of the base ceramic varistor.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Finally, in the last region (the high-current region) characterized by grain control, the current-voltage characteristics are linear again as occurs in the first region. Since zinc oxide [ZnO] material was introduced by Matsuoka (1971), it has been the most extensively studied material and used as the base for ceramic systems, consequently it became the most important ceramic for commercial production of varistors (Clarke, 1999;Peiteado, 2005;Wang et al, 2003;Kale et al, 1999;Matsuoka, 1971). Due to the need of attaining varistors with better properties, there has recently been a great interest in other ceramic materials, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Estos materiales actúan como dispositivo para la protección de equipos electrónicos y su función es desviar los sobrevoltajes; la principal función de estos dispositivos es mantener el valor de potencial eléctrico cuando ocurre un gran aumento en la intensidad del campo eléctrico aplicado (1). Esto se puede expresar a través de la ecuación I=KV α , donde α es el coeficiente de no-linealidad, parámetro muy importante para la caracterización de los varistores (2).…”
Section: Introductionunclassified